Chapter 1: Understanding environmental politics in a turbulent era - Shipton, Leah (Edward Elgar Publishing, 2023)
While turbulence is a longstanding feature of world politics, contemporary turbulence stemming from climate change and accompanying environmental catastrophes, and interacting with developments in other areas of international politics, has more dire planetary consequences than ever before. Yet, the subfield of global environmental politics has not systematically examined turbulence and its consequences. This chapter lays a beginning foundation for understanding turbulence and global environmental politics. It begins by defining turbulence, including by distinguishing it from crisis and identifying its key elements. Next, the chapter explores sources of turbulence, beginning with its roots in the political and economic world order, before reviewing more "downstream" sources of turbulence, such as actor behavior and the events, trends, and policies that an actor faces from its broader setting. The chapter concludes with a discussion of who experiences turbulence and how the negative consequences of turbulence disproportionately burden marginalized groups.